Prevalence of Metabolic Syndrome in Hypertensive De Novo Patients at a Tertiary Care Hospital - Govindula, Anusha; Valupadas, Chandrasekhar; Panchagiri, Sabitha (Indian Journal of Pharmacy Practice)
Background: Hypertension is a significant risk factor for the development of cardiovascular disease (CVD), a leading cause of mortality worldwide. Increasing blood pressure could be a marker for metabolic syndrome (MtS) usually undiagnosed, together, which intensify the risk of future development of CVD. Methodolodgy: Present prospective, open labeled, observational study was conducted at outpatient department of Mahatma Gandhi Memorial Hospital in Warangal, Telangana, India. The study was carried out for four months, from June 2013 to September 2013. Patients who met the study preset criteria and consented were enrolled and the entire parameters essential for evaluation of MtS were done by using standard techniques from the protocol. Results: A total of 120 hypertensive patients (75 male; 45 female) with mean age of 53.28 ± 12.98 years was examined. When classified according to National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) for MtS, 82.5% were falling in this criterion. Of this total, 43%, 30.8% and 8.33% were met with HTN with 2, HTN with 3 and HTN with 4 criteria respectively. Conclusion: A significant prevalence of MetS among newly diagnosed hypertensive patients was observed. In view of this there is a need to screen all hypertensive patients for the abnormalities at the time of diagnosis and an effective action plan is needed to combat MtS in order to prevent its consequences.
Keywords: Hypertension; Metabolic Snydrome; National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III)